Meme kanseri ameliyatlarından sonra lenfödemin önlenmesinde basit lenf drenajı masajı ile aromatik yağlarla yapılan basit lenf drenajı masajının karşılaştırılması - Gül, Asiye Taş (My University, 2005)
Çalışma, meme kanseri ameliyatlarından sonra lenfödemin önlenmesinde basit lenf drenajı (BLD) masajı ile aromatik yağlarla yapılan basit lenf drenajı masajının etkisini belirlemek amacıyla tanımlayıcı-karşılaştırmalı olarak yapıldı. Araştırmanın evrenini iki üniversite hastanesinde, meme kanseri nedeniyle meme koruyucu tedavi veya modifiye radikal mastektomi ile birlikte aksiller diseksiyon uygulanan hastalar oluşturdu. Kontrol grubuna (1. grup) 23, BLD masajı uygulanan gruba (2. grup) 21, aromatik yağlarla BLD masajı uygulanan gruba (3. grup) 20 olmak üzere, örnekleme toplam 64 hasta alındı. Veriler, Bireysel Özellikler Formu ve Lenfödem İzlem Formu aracılığıyla toplandı. Tüm hastaların ameliyat öncesi, taburcu olmadan önce, ameliyat sonrası ikinci, dördüncü ve altıncı ayda dört farklı noktadan kol çevreleri ölçüldü, kolda lenfödeme yönelik uyuşukluk, gerginlik, ağrı, harekette sınırlılık ve ödem yakınmaları değerlendirildi. Verilerin değerlendirilmesinde ortalama, yüzdelik, ki-kare, Fisher kesin olasılık testi, Wilcoxon testi, Kruskal-Wallis tek yönlü varyans analizi ve Dunn testi kullanıldı. Araştırmadan elde edilen sonuçlara göre; ameliyat sonrası 2. ve 4. ayda, koldaki ağrı ve harekette sınırlılık yakınmaları açısından 1. grup ile 2. ve 3. grup arasında istatistiksel olarak anlamlı (p<0.05) fark olduğu belirlendi. 1. gruptaki hastaların %30.4 (n=7)'ünde 2. ayda, %17.4 (n=4)'ünde 4.ayda, %21.7 (n=5)'sinde 6. ayda, 2. gruptaki hastaların %19 (n=4)'unda 2., 4. ve 6. ayda, 3. gruptaki hastaların ise %5 (n=1)'inde yalnızca 2. ayda lenfödem geliştiği belirlendi. 1. grupta daha fazla olmakla birlikte, örneklemi oluşturan tüm hastaların etkilenen kol çevrelerinde artış olduğu belirlendi. Sonuç olarak, lenfödemi önlemeye yönelik uygulanan BLD masajı ve aromatik yağlarla yapılan BLD masajının yakınmaları ve lenfödemi azaltmada etkili olduğu, bu nedenle, meme kanserli hastalara BLD masajının ve aromatik yağlarla yapılan BLD masajının yaygınlaştırılmasının yararlı olacağı düşünülmektedir. Modifiye radikal mastektomi, meme koruyucu tedavi, lenfödem, basit lenf drenajı masajı, aromatik yağlarla yapılan basit lenf drenajı masajı.

The study was carried out as a descriptive- comparative research to determine the effect of simple lymph drainage massage and simple lymph drainage massage with aromatic oils for the prevention of lymphedema after breast cancer operations. The universe of the study was formed of patients, who had modified radical mastectomy or breast conserving surgery together with axillary dissection because of breast cancer, in two university hospitals. A total of 64 patients, which consisted of 23 in control group (1st. group), 21 in the group (2th. group) who had simple lymph drainage massage and 20 in the group (3th. group) who had simple lymph drainage massage with aromatic oils, were taken in the sample group. The data were collected by Individual Characteristics Form and Lymphedema Observation Form. The arm circumferences of all the patients were measured at four different points before the operation, before discharge from hospital, in the 2nd, 4th. and 6th. months after operations and the complaints of numbness, tightness, pain, limited motion and edema as the results of lymphedema were considered. In the evaluation of data, mean, percentages, chi-square, Fisher's exact test, Wilcoxon test, Kruskal- Wallis One-way ANOVA and Dunn test were used. According to the results of the study; the difference between the 1st. group and 2th.-3rd. groups was statistically significant (p<0.05) in terms of pain and limited motion complaints on the arm in the 2nd. and 4th. months after the operation. It was found that lymphedema occured in the 1st. group in the 30.4% (n=7) of the patients in the 2nd. month, in 17.4% (n=4) in the 4th. month, in 21.7% (n=5) in the 6th. month, in the 2nd. group in the 19% (n=4) of the patients in the 2nd., 4th. and 6th. months and in the 3rd. group in the 5% (n=1) of the patients only in the 2nd. month. It was seen that there was increase in the arm circumferences of all the patients forming the 2nd. and 3rd. groups although the highest increase was in the 1st. group. As a result it is thought that simple lymph drainage massage and simple lymph drainage massage with aromatic oils, which are applied to prevent lymphedema, were effective to decrease lymphedema and the widespreading of simple lymph drainage massage and simple lymph drainage massage with aromatic oils applications to the patients having breast cancer could be helpful. Key Words: Modified radical mastectomy, breast conserving surgery, lymphedema, simple lymph drainage massage, simple lymph drainage massage with aromatic oils.
Keywords: Aromaterapi; Cerrahi Hastalıkları Hemşireliği; Lenfödem; Meme Kanseri Tedavisi